THE ILLOCUTIONARY ACTS AND THE TRANSLATION TECHNIQUES IN SHERLOCK HOLMES MOVIE SERIES - Tambunan, Sunarti Desrieny (Universitas Gunadarma, 2020)
Understanding the context of the speech act is very important before translating it into its target language. Therefore, this research aims at: (1) finding out the types of illocutionary acts produced by Sherlock Holmes and (2) discovering the translation techniques used in translating Sherlock Homes’ illocutionary acts. This research is a descriptive qualitative. The results show that there are 132 illocutionary acts found in the movie. From 18 translation techniques proposed by Molina and Albir, there are only eight translation techniques used by the subtitler to translate the illocutionary acts. Those translation techniques are amplification, adaptation, discursive creation, modulation, literal, particularization, reduction, and transposition.